Investigating Elite End-of-Athletic-Career Transition: A Systematic Review. Issue 3 (2nd July 2016) - Knights, Sophie; Sherry, Emma; Ruddock-Hudson, Mandy
Abstract : This article presents a systematic review of the literature investigating factors that contribute to a successful end-of-career transition among elite athletes. The systematic review included 10 studies that focused on elite athlete retirement that in part measured positive outcomes, which fall under the flourishing construct. Results indicated that although there has been an abundance of research examining multiple effects of transition out of sport among elite athletes, there appears to be no current literature explicitly examining flourishing within this elite population. The results of the review have practical implications for sport psychology practitioners who are aiming to facilitate a successful transition for elite athletes through their end-of-athletic-career transition. The findings from the systematic review are discussed, and the article provides recommendations for future research and for current applied practice.